2018
DOI: 10.1021/acs.jafc.8b02233
|View full text |Cite
|
Sign up to set email alerts
|

Green and Black Tea Phenolics: Bioavailability, Transformation by Colonic Microbiota, and Modulation of Colonic Microbiota

Abstract: Monomeric green tea catechin (GTC) and oligomeric, oxidized black tea phenolic (BTP) have shown promising health benefits, although GTC has been more extensively studied than BTP. We review the current knowledge on bioavailability, colonic transformation, and gut microbiota modulatory effects of GTC and BTP. As a result of their similar poor bioavailability in the small intestine and potentially similar metabolites upon colonic fermentation, it seems as if GTC and BTP have similar health effects, although it c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
84
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(86 citation statements)
references
References 44 publications
2
84
0
Order By: Relevance
“…The microbiota inhabiting the intestinal cavity affects body health by altering the metabolome and regulating the bacterial bioavailability of nutrients in the lumen. ( Johnson et al, 2015 ; Liu et al, 2018 ; Romano et al, 2015 ). In this study, we observed a significant association between the gut microbiota and the variation in BMI and blood lipid levels, which is independent of age.…”
Section: Discussionmentioning
confidence: 99%
“…The microbiota inhabiting the intestinal cavity affects body health by altering the metabolome and regulating the bacterial bioavailability of nutrients in the lumen. ( Johnson et al, 2015 ; Liu et al, 2018 ; Romano et al, 2015 ). In this study, we observed a significant association between the gut microbiota and the variation in BMI and blood lipid levels, which is independent of age.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally believed that the bioavailability of phenolic substances in human body is low in comparison to micro and macronutrients, especially for TP (Liu, Bruins, Ni, & Vincken, 2018), because the molecular weight of TP is relatively high and has lots of hydrogen bonds to the hydroxyl group (Warden, Smith, Beecher, Balentine, & Clevidence, 2001). Studies have demonstrated that only a few tea F I G U R E 3 Absorption and biotransformation of tea catechins catechins can be straightly absorbed by small intestine, while most of them (about 80%) may stay in gut and continue to intestinal bacteria metabolism (Warden et al, 2001).…”
Section: Tp Regulate the Bioavailability Of Intestinal Microorganismsmentioning
confidence: 99%
“… 11 Recent studies show that dietary intervention with phenolic compounds, most notably those from tea, red wine, or cocoa, promotes a more health-beneficial human gut microbiota composition. 12 14 Several in vitro and in vivo studies have indicated that green tea can promote the growth of beneficial bacteria, such as Bifidobacterium and Lactobacillus , and inhibit pathogenic bacteria, such as Clostridium . 15 17 …”
Section: Introductionmentioning
confidence: 99%